Implementation of Kodular for Developing an Online Attendance System at Bhakti Bangsa Junior High School - Tanjung, Khairil Imam Amri; Harahap, Baginda; Rambe, Aripin (Journal of Technology and Computer, 2026)
Attendance is a crucial component of educational administration, closely related to teacher discipline and accountability. However, at SMP Bhakti Bangsa Sunggal, attendance is still conducted manually, often leading to delayed recapitulation, recording errors, and data manipulation. This research aims to develop an Android-based teacher attendance application utilizing the Kodular platform integrated with Google Sheets/Firebase as a digital solution that is efficient, transparent, and accurate. The research employed a Research and Development (R&D) approach with the System Development Life Cycle (SDLC) Waterfall model, which consists of needs analysis, system design, implementation, testing, and maintenance. The resulting application includes features such as user login, attendance through QR-Code scanning, automatic attendance recording, daily and monthly attendance reports, and exporting reports in Excel/PDF format. Black-box testing confirmed that all functions operated properly. Furthermore, trials involving 22 teachers and one administrative staff member showed “very good” responses, with scores of 93% for ease of use, 89% for speed, 91% for accuracy, and 92% for user satisfaction. Based on these findings, the Kodular- based attendance application is proven feasible and effective in replacing the manual system at SMP Bhakti Bangsa Sunggal. The application enhances administrative efficiency, improves data accuracy, and supports the school’s digital transformation in managing teacher attendance.